2011
DOI: 10.1089/neu.2011.1885
|View full text |Cite
|
Sign up to set email alerts
|

Visual Pursuit: Within-Day Variability in the Severe Disorder of Consciousness

Abstract: Visual pursuit marks substantial recuperation from a vegetative state and evolution into a minimally-conscious state, but its incidence in different studies suggests some unreliability in contrast with its established prognostic relevance. Subjects in vegetative (n=9) or minimally-conscious (n=13) states were tested for visual pursuit 6 times/day (9:30, 10:30, and 11:30 am, and 2:00, 3:00, and 4.00 pm, for a total of 132 determinations). Visual pursuit was observed at all testing times in 8 minimally-conscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 41 publications
1
59
1
Order By: Relevance
“…Moreover, unsettled vigilance could also have impacted both studies by negatively affecting both the patients' performance and diagnosis. Indeed, a recent study showed that visual pursuit is particularly sensitive to withinday fluctuations in patient with MCS [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unsettled vigilance could also have impacted both studies by negatively affecting both the patients' performance and diagnosis. Indeed, a recent study showed that visual pursuit is particularly sensitive to withinday fluctuations in patient with MCS [39].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known, however, that vigilance and awareness fluctuate in such patients, resulting in variable behaviors and cognitive performances. [2][3][4] At present, there is no standard description of the different vigilance states in VS/UWS and MCS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of caregivers may decrease misdiagnosis percentage [22]. Within-day variability of diagnosis was high: it may achieve 33% in the VS/UWS and 38% in MCS [23]. What important assessment using GCS do not provide predictor that a patient is emerging from VS/UWS to an MCS [14].…”
Section: Management Of Patients With Docmentioning
confidence: 99%